Heavy gaming: is your brain at risk of permanent damage? / Yusandra Md Yusoff and Emmy Nurashikin Ismail Hashim - Md Yusoff, Yusandra; Ismail Hashim, Emmy Nurashikin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Playing video games too much can be bad for your mental health.” Gaming is undoubtedly an exciting experience. It is easy to lose track of time while immersed in intense combat or exploring new worlds. However, while gaming can provide a delightful escape, excessive gaming can have harmful effects that are often overlooked. Let us explore the dangers of excessive gaming in more detail, particularly when it develops into Internet Gaming Disorder or IGD. Internet Gaming Disorder (IGD): What is it? Internet Gaming Disorder (IGD) is far more than just a term for excessive gaming. In this condition, gaming dominates your life, pushing aside social connections, meals, and even sleep. Individuals with IGD often play for prolonged periods—even days—without adequate sleep. Over-gaming has led to dire consequences, with 24 reported fatalities worldwide [1].